Low preserved proximal femoral bone stock volume as a risk factor for periprosthetic femoral fractures. A study of 90 femurs - Kolar, Matic; Mavčič, Blaž; Kralj-Iglič, Veronika; Antolič, Vane (Frontiers in Surgery, 2025)
BackgroundDespite the longstanding awareness of the increasing incidence and consequences of periprosthetic proximal femoral fractures (PPFFs), and the rationale protective role of the preserved bone stock, no method for its evaluation, with the potential for routine clinical application, has been available. A novel method for the evaluation of preserved proximal femoral bone stock volume (VPF) in conventional primary total hip arthroplasty (THA) on routinely available hip radiographs was introduced and compared with clinical data.MethodsStudy was designed according to the standard protocol for retrospective matched case-control research. 30 cases of late PPFFs (minimum 1 year postoperatively) were identified in the hospital database of all implanted Anatomic Benoist Girard (ABG) II femoral stems. For every case, 2 age-/sex-/implant size-/surgeon-matched controls were found. The VPF was evaluated for each hip, and the mean values in both groups were compared. The accuracy and intra-/inter-rater reliability of the novel method were tested. Regression subanalyses were performed to identify factors influencing the risk of PPFFs, and to assess correlations between VPF and other covariables.ResultsThe mean VPF in the group of cases was 113.8 ± 21.0 cm3 and significantly lower compared to 164.0 ± 38.4 cm3 in the control group (P < 0.01). The method's reliability and accuracy were within good to excellent range. The VPF was the sole significant factor influencing the risk of PPFFs (aOR = 0.92). The cut-off value was determined at 128.5 cm3. The regression analysis indicated an interplay of intuitively connected factors in the long-term PPFFs prognosis (VPF, stress shielding, subsidence).ConclusionsThe presented results indicate that bone stock preservation (with VPF as a quantitative measure) is crucial for the prevention of late PPFFs.